2011
DOI: 10.1038/bmt.2011.53
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of folinic acid in preventing oral mucositis in allogeneic hematopoietic stem cell transplant patients receiving MTX as prophylaxis for GVHD

Abstract: [Running title] Effect of folinic acid on oral mucositis[Key words] oral mucositis, folinic acid, stem cell transplantation -2 - AbstractSince the safety of folinic acid administration and its efficacy for reducing the toxicity of methotrexate (MTX) remain controversial, we assessed the effect of folinic acid administration after MTX treatment for GVHD prophylaxis on the incidence of oral mucositis and acute GVHD. We retrospectively analyzed data for 118 patients who had undergone allogeneic hematopoietic stem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 24 publications
1
22
0
2
Order By: Relevance
“…(67.4%). However, it is above the rates found in more recent studies . Despite the innumerable variables interfering in the comparison between the samples of these studies, there appears to be a current trend in the literature to lower frequencies of severe degrees of OM, even without direct therapeutic interference in OM.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…(67.4%). However, it is above the rates found in more recent studies . Despite the innumerable variables interfering in the comparison between the samples of these studies, there appears to be a current trend in the literature to lower frequencies of severe degrees of OM, even without direct therapeutic interference in OM.…”
Section: Discussionmentioning
confidence: 56%
“…The frequency of grades III and IV of OM in patients of group II, without laser (61.8%), was similar to that reported by Wardley et al [15] (67.4%). However, it is above the rates found in more recent studies [14][15][16][17]. Despite the innumerable variables interfering in the comparison between the samples of these studies, there appears to be a current trend in the literature to lower frequencies of severe degrees of OM, even without direct therapeutic Table 3.…”
Section: Discussionmentioning
confidence: 77%
“…Due to the high TRM rate, it is not acceptable to consider HSCT as the standard treatment option for patients with DS‐ALL. Discovering appropriate GVHD prophylaxis is one of the solutions to improve survival, such as the use of folinic acid after administering the MTX dose which might allow the use of standard doses of MTX . Reducing the intensity of the conditioning regimens is another conceivable option, although it might be associated with an increased risk of ALL relapse.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, the administration of folinic acid may reduce the incidence of oral mucositis [24]. Several studies have reported that the systemic administration of folinic acid, which is routinely used to mitigate MTX toxicities, potentially reduces the incidence of severe oral mucositis after HSCT [25][26][27]. The incidence of GVHD in Japanese patients is lower than that in Caucasians [28,29], possibly due to the more homogenous genetic background of the Japanese population [30].…”
Section: Discussionmentioning
confidence: 99%